The Effect of Manufacturing Firms' Spatial Distributions and Entrepreneurships on the Productivity of Manufacturing Industries: An Empirical Study on Korean Case - Jichung Yang; Daeyoung Park; Changmu Jung (European Regional Science Association (ERSA), 2010)
In this paper, the spatial distributions of firm and entrepreneurship were investigated in relation with the productivity. To analyze the effect of manufacturing firms' detailed distribution patterns on the productivity of manufacturing industries, micro geographic data were used, which avoids systematic problems relating scales and borders of box unit that is administrative territories. First of all, agglomeration distances for every sub-industries were estimated, that is spatial boundaries of localization effect. Three main variables relating spatial distribution patterns of firms in same industrial classification, that are the number of firms, the average distance to other firms and disperse index from standard deviation of firms' Euclidian coordinates, are computed from Euclidian coordinates of firms in the agglomeration boundaries. Also, we checked the relationship between Entrepreneurships and productivity. And mixed effects were checked. These tests were applied to an exhaustive manufacturing firms data-set of Korea including Seoul Metropolitan Area provided by NSO. We can predict that for most sub-industries, (i) the number of firms of the same industrial classification in the agglomeration boundary has positive effect on the productivity, (ii) the average distance to other firms has positive effect below the specific distance and negative effect beyond that, and (iii) the more disperse the firms are, productivity gets decreased
Keywords: 330